Georgia Architectural and Historic Properties Survey of Warmack Furniture and Mercantile Co., 101 E. Screven Ave., Quitman, Brooks County, Ga., 1981 - Bartholomew and Smith (South Georgia Area Planning and Development Commission, 1981)
Georgia Architectural and Historic Properties Survey of Warmack Furniture and Mercantile Co., 101 E. Screven Ave., Quitman, Brooks County, Ga., 1981. Three story commercial brick building of rectangular plan. Flat roof. Double hung sash windows with 2/2 lights. Third story windows shuttered in. Small pediment over each. Cast iron cornice at parapet with dentil range. Good condition. Date of Construction: Jan. 21st, 1898. In 1980, this was the Livingston Snow Co., a pecan shelling and packing co. Significant as part of a potential National Register district, a downtown district of mostly 19th century buildings on Screven St.
Georgia Architectural and Historic Properties Survey of Warmack Furniture and Mercantile Co., 101 E. Screven Ave., Quitman, Brooks County, Ga., 1981. 1 electronic record and assets. Digitized from originals. 1 PDF. 3 scans. 1 photograph. 3200 DPI TIF. 300 DPI 4x6 JPG. 81.0 MB (85,022,504 bytes).
Keywords: Historic buildings; Real property surveys; Lowndes County Historical Society (Lowndes County, Ga.); Quitman (Ga.); Brooks County (Ga.)